2014
DOI: 10.3409/fb62_1.59
|View full text |Cite
|
Sign up to set email alerts
|

<I>In Vitro</I> Effects of Quercetin on Oxidative Stress Mediated in Human Erythrocytes by Benzoic Acid and Citric Acid

Abstract: Benzoic acid (BA) and citric acid (CA) are food additives commonly used in many food products. Food additives play an important role in food supply but they can cause various harmful effects. The in vitro adverse effects of BA and CA and the protective effect of quercetin on human erythrocytes were investigated by measuring malondialdehyde (MDA) levels and superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) and glutathione-S-transferase (GST) activities. Erythrocytes were incubated with BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Antioxidant enzymes are important cell protectors against oxidative stress induced injuries. The principal endogenous antioxidants that show effects on ROS are SOD, GPx, GST, and CAT (Baş et al, ). The activities of these enzymes have been used to evaluate oxidative stress in cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antioxidant enzymes are important cell protectors against oxidative stress induced injuries. The principal endogenous antioxidants that show effects on ROS are SOD, GPx, GST, and CAT (Baş et al, ). The activities of these enzymes have been used to evaluate oxidative stress in cells.…”
Section: Discussionmentioning
confidence: 99%
“…The GPx protects cell membranes from oxidative damage via catalyses H 2 O 2 conversion to H 2 O. SOD and CAT catalyze the dismutation of superoxide anions to the oxygen and H 2 O 2 , H 2 O 2 conversion to the water like as GPx respectively (Messarah et al, ). GST catalyzes the conjugation of several electrophilic substrates to the thiol group of GSH so it produces less toxic forms (Baş et al, ). Heavy metals have adverse effects on antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SOD catalyzes the dismutation of superoxide radicals to hydrogen peroxide and molecular oxygen [ 10 ].CAT catalyzes the reduction of H 2 O 2 to water and oxygen and protects the cell against H 2 O 2 induced oxidative damage [ 11 ]. The GPx and GST catalyse the reduction of H 2 O 2 to H 2 O and the conjugation of electrophilic substrates to the thiol group of GSH so it produces less toxic forms, respectively [ 12,13 ]. Male germ cells are more susceptible to oxidative stress than other cells, because they have higher polyunsaturated fatty acids in their membranes than somatic cells.…”
Section: Introductionmentioning
confidence: 99%
“…GSH-Px is a peroxide decomposition enzyme, using glutathione (GSH) as a substrate to transformH et al, 2013). GST is provided with antioxidation and detoxification, transforming toxic materials into less toxic forms(Mansour and Mossa.2010) Baş et al (2014). have reported that 50, 100 and 200 μg/mL benzoic acid may induce oxidative stress in the human erythrocytes.…”
mentioning
confidence: 99%